2017
DOI: 10.1093/ofid/ofx163.125
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pathogens Directly From Diabetic Foot Infections by Shotgun Metagenomic Sequencing

Abstract: Background Diabetic foot infections (DFIs) constitute the most common cause for diabetes-related hospitalization and lower extremity amputations. Current diagnostic methods are slow and in some cases do not detect all potential pathogens. Metagenomics sequencing has the potential to merge rapidity and comprehensive information about causative pathogens in DFIs. The aim of this study was to evaluate the potential of metagenomics strategies for DFIs.Methods Thirty tissue specimens from patients with neuropathic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The Qiagen-based method becomes popular in the microbiome study field for various sample types. [22][23][24][25] More recently, the Omega Mag-Bind Stool extraction protocol 26,27 has drawn researchers' attention; Mackenzie et al previously reported that the Qiagen DNeasy PowerSoil Kit is the most effective human fecal microbial DNA extraction method when compared with the HMP extraction method, QIAamp® DNA Stool Mini Kit, ZR Fecal DNA MiniPrep™, and 1 non-kit phenol: chloroform-based DNA isolation protocol. 28 According to previous studies, 29 bead beating method is more robust than non-bead-beating-based protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The Qiagen-based method becomes popular in the microbiome study field for various sample types. [22][23][24][25] More recently, the Omega Mag-Bind Stool extraction protocol 26,27 has drawn researchers' attention; Mackenzie et al previously reported that the Qiagen DNeasy PowerSoil Kit is the most effective human fecal microbial DNA extraction method when compared with the HMP extraction method, QIAamp® DNA Stool Mini Kit, ZR Fecal DNA MiniPrep™, and 1 non-kit phenol: chloroform-based DNA isolation protocol. 28 According to previous studies, 29 bead beating method is more robust than non-bead-beating-based protocol.…”
Section: Discussionmentioning
confidence: 99%